THE RISE OF BIOCRAMICS IN ENDODONTICS : A REVIEW - PRATISHTA JAIN; MANISH RANJAN (International Journal of Pharma and Bio Sciences, 2015)
Bioceramics are biocompatible ceramic materials, which are being used for various procedures in the medical and dental field. They include alumina, zirconia, bioactive glass, glass ceramics, coatings and composites, hydroxyapatite, resorbable calcium phosphates and radiotherapy glasses. They are ceramic or metal oxides with enhanced biocompatibity, sealing ability, antibacterial and antifungal activity. They have the ability to either function as human tissues or to resorb and encourage the regeneration of natural tissues. At present, bioceramics have a wide array of surgical, endodontic and prosthodontic applications in dentisry. In this review, we discuss about its various uses in endodontic procedures which include as sealer, for root repair and pulp caping and in periapical surgeries.Further clinical research is required to make it the material of choice.